A Prediction Method of Coal Burst Based on Analytic Hierarchy Process and Fuzzy Comprehensive Evaluation - Zhu, Zhijie; Wu, Yunlong; Han, Jun (Frontiers in Earth Science, 2022)
Coal burst has become a worldwide problem that needs to be solved urgently for the sake of coal mine safety production due to its complicated triggering mechanisms and numerous influencing factors. The risk assessment of coal burst disasters is particularly critical. In this work, 15 factors affecting coal burst occurrence are selected from the perspectives of geodynamic environment, geological and mining conditions and the influence mechanism of each factor on coal bursts is analyzed. An evaluation index system of coal burst risk is put forward. A hierarchical model of coal burst prediction is established and the weight of each influencing factor to coal burst risk is calculated. Based on the fuzzy comprehensive evaluation method, a coal burst prediction model is established, which can scientifically decompose and simplify the complicated problem and make coal burst prediction and prevention more pertinent and effective. The model is applied to assess the coal burst risk level of a coal mine in Shanxi Province and the evaluation result is consistent with practical situations. This method considers the influencing factors comprehensively and determines the weight of each factor scientifically compared with other forecasting methods.